Диагностика, видовая самостоятельность и распространение Halicyclops septenirionalis Кiеfеr (Crustacea, Copepoda) - Монченко, В.И. (Вестник зоологии, 1979)
Halicyclops septentrionalis was found in the Karkinitsky bay of the Black Sea and in two islands of the Sea of Azov. All the populations are biometrically undistinguishable. The cohabitation with H. rotundipes and the establishment of 14 essential differences with the last one prove the species independence of H. septentrionalis. It is the first record of this species in the fauna of the both seas and in the Soviet Union.